Global evaluation of key factors influencing nitrogen fertilization efficiency in wheat: a recent meta-analysis (2000-2022) - Yokamo, Solomon; Irfan, Muhammad; Huan, Weiwei; Wang, Bin; Wang, Yiliu; Ishfaq, Muhammad; Lu, Diajun; Chen, Xiaoqin; Cai, Qiuliang; Wang, Huoyan (Frontiers in Plant Science, 2023)
Improving nitrogen use efficiency (NUE) without compromising yield remains a crucial agroecological challenge in theory and practice. Some meta-analyses conducted in recent years investigated the impact of nitrogen (N) fertilizer on crop yield and gaseous emissions, but most are region-specific and focused on N sources and application methods. However, various factors affecting yield and N fertilizer efficiency in wheat crops on a global scale are not extensively studied, thus highlighting the need for a comprehensive meta-analysis. Using 109 peer-reviewed research studies (published between 2000 and 2022) from 156 experimental sites (covering 36.8, 38.6 and 24.6% of coarse, medium, and fine-textured soils, respectively), we conducted a global meta-analysis to elucidate suitable N management practices and the key factors influencing N fertilization efficiency in wheat as a function of yield and recovery efficiency and also explained future perspectives for efficient N management in wheat crop. Overall, N fertilization had a significant impact on wheat yield. A curvilinear relationship was found between N rates and grain yield, whereas maximum yield improvement was illustrated at 150-300 kg N ha-1. In addition, N increased yield by 92.18% under direct soil incorporation, 87.55% under combined chemical and organic fertilizers application, and 72.86% under split application. Sitespecific covariates (climatic conditions and soil properties) had a pronounced impact on N fertilization efficiency. A significantly higher yield response was observed in regions with MAP > 800 mm, and where MAT remained < 15 oC. Additionally, the highest yield response was observed with initial AN, AP and AK concentrations at < 20, < 10 and 100-150 mgkg-1, respectively, and yield response considerably declined with increasing these threshold values. Nevertheless, regression analysis revealed a declining trend in N recovery efficiency (REN) and the addition of N in already fertile soils may affect plant uptake and RE. Global REN in wheat remained at 49.78% and followed a negative trend with the further increase of N supply and improvement in soil properties. Finally, an advanced N management approach such as "root zone targeted fertilization" is suggested to reduce fertilizer application rate and save time and labor costs while improving NUE in wheat production.